A Biobattery Capsule for Ingestible Electronics in the Small Intestine: Biopower Production from Intestinal Fluids Activated Germination of Exoelectrogenic Bacterial Endospores. Issue 1 (28th November 2022) - Rezaie, Maryam; Rafiee, Zahra; Choi, Seokheun
Abstract: Functioning ingestible capsules offer tremendous promise for a plethora of diagnostic and therapeutic applications. However, the absence of realistic and practical power solutions has greatly hindered the development of ingestible electronics. Microbial fuel cells (MFCs) hold great potential as power sources for such devices as the small intestinal environment maintains a steady internal temperature and a neutral pH. Those conditions and the constant supply of nutrient‐rich organics are a perfect environment to generate long‐lasting power. Although previous small‐scale MFCs have demonstrated many promising applications, little is known about the potential for generating power in the human gut environment. Here, this work reports the design and operation of a microbial biobattery capsule for ingestible applications. Dormant Bacillus subtilis endospores are a storable anodic biocatalyst that will provide on‐demand power when revived by nutrient‐rich intestinal fluids. A conductive, porous, poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate hydrogel anode enables superior electrical performance in what is the world's smallest MFC. Moreover, an oxygen‐rich cathode maintains its effective cathodic capability even in the oxygen‐deficit intestinal environment. As a proof‐of‐concept demonstration in stimulated intestinal fluid, the biobattery capsule produces a current density of 470 µA cm −2 and a power density of 98 µW cm −2, ensuring its practical efficacy as a novel and sole power source for ingestible applications in the small intestine. Abstract : Microbial fuel cells (MFCs) hold great potential as power sources for ingestible electronics as the small intestinal environment maintains a steady internal temperature and a neutral pH. A proposed ingestible MFC capsule leverages the bacterial survival strategy of becoming dormant endospores under adverse environments and germinating when sufficient nutrients are available. The capsule provides significant power and current.